Comparative Study on Type II Gypsum and Heat Cure Roughness in Ammonium Bicarbonate Solution - Ashwini Rani SR (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background:The chemical decomposition of POP idols using an NH4HCO3 solution produces valuable products with efficient use of ammonium and without any negative effects.Aim: To evaluate the dissolution of type II CaSO4 .2 H2O & its effect on SR of HC-AR immersed in different concentrations of NH4HCO3 solution. Material & method: A total of 40 samples were included with 4 groups A,B,C,D . Group D was control with distal water while group A,B,C with 1:1,1:2 and 1:3 concentration of NH4HCO3 , POP and 150 ml of water. Result: We discovered a statistically non-significant change seen in surface roughness on inter comparison of groups of acrylic plates arch in all groups, namely A, B, C, and D, at various time intervals (i.e., 0 to 12 hrs and 0 to 48 hrs). Conclusion: No change regarding SR on HC-AR at diiferent times for type II POP.